People, transports and the spread of the Argentine and in Europe, from c.1850 to the present - Queiroz, Ana Isabel; Alves, Daniel (CEM – Cultura, Espaço & Memória, 2018)
Environmental history is increasingly contributing to the research on bioinvasions. It investigates the vectors of introduction, people’s perceptions and societal responses. Historical narratives of introduction processes and spread may help improve current preventive and management practices designed to mitigate impacts in the economy, ecology and people’s well-being. In this framework, we study the introduction of the Argentine ant (Linepithema humile Mayr) in Europe since the nineteenth century when the species was perceived as inconvenient and harmful. A narrative of the expansion combines historical material from different sources, origins and scales and examines pathways through time. We conclude that the species arrived to different regions of Europe through independent processes, associated with travel and trade, and strictly connected with the evolution of transportations.